EVALUATION OF THE FEET IN DIABETIC INDIVIDUALS AND THE LEVEL OF PERIPHERAL NEUROPATHY (Fiep Bulletin - online, 2014)
The Diabetes Mellitus (DM) is an important problem with public health and can be associated with complications. The feet constitute a big factor inside the chronic complications that a diabetic is exposed to and deserves special attention, since they present a great potential to produce incapacity. The present study was realized with seven cases of diabetes type 2 through clinical assessment of the feet in which was evaluated the sole sensibility and the level of peripheral neuropathy. The results demonstrated that all the participants had areas of loss of sensibility and that the level of neuropathy varied from light to severe. These individuals lack of basic information for the prevention of injuries, care with the feet and need a better orientation by the health professionals.
Keywords: Diabetes Mellitus; Level of neuropathy; Sole sensibility.